Lamna nasus - Carneiro, Miguel; Martins, Rogélia; Landi, Monica; Costa, Filipe O. (Zenodo, 2014)
* □ Lamna nasus (Bonnaterre, 1788) – Porbeagle; Tubarão-sardo ① , Marracho ②③ The species L. nasus is indicated as native to Madeira (Compagno 1984a), although Wirtz et al . (2008) considered the presence of this species off Madeira as doubtful. : Published as part of Carneiro, Miguel, Martins, Rogélia, Landi, Monica & Costa, Filipe O., 2014, Updated checklist of marine fishes (Chordata: Craniata) from Portugal and the proposed extension of the Portuguese continental shelf, pp. 1-73 in European Journal of Taxonomy 73 on page 11, DOI: 10.5852/ejt.2014.73, http://zenodo.org/record/3866515 : {"references": ["Compagno L. J. V. 1984 a. FAO Species Catalogue. Sharks of the world. An annotated and illustrated catalogue of shark species known to date. Part 1 - Hexanchiformes to Lamniformes. FAO Fisheries Synopsis 125: 1 - 249, Rome.", "Wirtz P., Fricke R. & Biscoito M. J. 2008. The coastal fishes of Madeira Island - new records and an annotated check-list. Zootaxa 1715: 1 - 26."]}